Generation of High-Order Vortex States From Two-Mode Squeezed States - Puentes, Graciana; Banerji, Anindya (Frontiers in Physics, 2021)
We report a scheme for generation of high-order quadrature vortex states using two-mode photon-number squeezed states, generated via the non-linear process of Spontaneous Parametric Down Conversion. By applying a parametric rotation in the quadratures (X,Y), using a φ converter, the Gaussian profile of the photon-number squeezed input state can be mapped into a superposition of Laguerre-Gauss modes in the quadratures with N vortices or singularities, for an input state containing 2N photons, thus mapping photon-number fluctuations to interference effects in the quadratures. Our scheme has the potential to improve measurement sensitivity beyond the Standard uantum Limit ( SQL N), by exploiting the advantages of optical vortices, such as high dimensionality or topological properties, for applications requiring reduced uncertainty, such as quantum cryptography, quantum metrology and sensing.